Vermiophis cangshanensis sp. nov., a new wormlion fly from Yunnan, China, with notes on its immature stages and biology (Diptera: Vermileonidae) - Li, Jia-Ling; Zhao, Can-Jun; Wang, Ji-Shen (Zootaxa, 2024)
Previously, the wormlion genus Vermiophis Yang, 1979 comprises seven known species, and all of them are endemic to China. We herein describe a new species, Vermiophis cangshanensis sp. nov. from Dali, Yunnan, China. The new species is closely similar to V. tibetensis Yang & Chen, 1987 in the general appearance, but can be differentiated from the latter by the wing venation and genitalia. In addition, the immature stages and biology of V. cangshanensis sp. n are described and briefly discussed. Keys are provided to separate the two genera of Vermileonidae recorded from China, and eight known species of Vermiophis. A distributional map is also presented for Vermiophis spp.